Đánh giá chất lượng đê, đập và cảnh báo biến động bất lợi dựa theo kết quả địa vật lý và mô hình tính cơ học - Nhu, Ngô Hương; Tuấn, Nguyễn Minh; Đông, Vũ Lâm; Cánh, Trần (Vietnam Journal of Earth Sciences, 2018)
To evaluate quality of dikes for warning disaster areas based on the combination ofgeophysical methods and mechanical calculating models